Risk Factors for Cardiovascular Diseases in School-going Adolescents between 13 and 17 Years. - Pinzón Gutiérrez, Claudia María; Navarro Toro, Claudia Inés; Tobón Borrero, Luz Miryam (Africa Journal of Nursing & Midwifery, 2023)
Introduction: Some authors have been able to determine that cardiovascular disease has its origins in early life stages and that the risk of suffering them is determined by the effect associated with exposure to cardiovascular risk factors over a long time, all of which produce a negative effect on the quality of life. Objective: We aimed to identify cardiovascular risk factors in schooled adolescents within public institutions of education in Villavicencio. Methods: This was a cross-sectional, prospective, observational study developed in eight high schools with children between 13 and 17 years old. A written standardised survey was applied (questionnaire type), which was auto-administered from the instrument denominated Global School-based Student Health Survey (GSHS) of the World Health Organisation (WHO). The modules were physical activity, eating behaviour, and drugs and alcohol consumption. In addition, the researchers took measures of weight, size, waist circumference, blood pressure and blood tests to measure total cholesterol, high-density lipoproteins (HDL), low-density lipoproteins (LDL), triglycerides and glucose, with each student's informed consent and that of his or her guardian. Statistics used were: average, standard deviation, interquartile ranges, proportions, Chi-square, and logistic regression. Results: A total of 1 504 students were analysed. Age and physical activity were not significantly associated with cardiovascular risk. Conclusions: The results allow us to establish that the predominant risk factors for cardiovascular disease in young adolescents between 13 and 17 years old school in high school in Villavicencio are: smoking, alcohol consumption, body mass index (BMI), and family antecedents (such as precursor pathologies and chronic renal insufficiency), the latter with a risk opportunity of 15.5 times of having cardiovascular disease in this population group.